2001
DOI: 10.1614/0890-037x(2001)015[0155:ssorts]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Sicklepod (Senna obtusifolia) Response to Shading, Soybean (Glycine max) Row Spacing, and Population in Three Management Systems1

Abstract: Studies were conducted in 1997 and 1998 at the Northeast Mississippi Research and Extension Center to investigate the effects of row spacing (76, 38, and 19 cm), soybean population, and three weed management systems on sicklepod growth and seed production. The cultivars ‘Hartz 5088RR’ (glyphosate-tolerant) and ‘Hutcheson’ (a conventional cultivar) were used in two separate studies. The average soybean populations over cultivars and year were 245,000 (low), 481,000 (medium), and 676,000 (high) plants/ha. The th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 25 publications
4
65
0
3
Order By: Relevance
“…The fraction of soil surface shaded by soybean canopy is influenced by crop row spacing and seeding rates (Renner and Mickelson, 1997;Nice et al, 2001), the angle of solar radiation inclination, crop variety, and environmental factors that affect plant growth. Todd et al (1991) showed that canopy shading played a more important role in reducing E s than straw mulch under dryland conditions.…”
Section: Crop Residue Cover and Canopy Shadingmentioning
confidence: 99%
“…The fraction of soil surface shaded by soybean canopy is influenced by crop row spacing and seeding rates (Renner and Mickelson, 1997;Nice et al, 2001), the angle of solar radiation inclination, crop variety, and environmental factors that affect plant growth. Todd et al (1991) showed that canopy shading played a more important role in reducing E s than straw mulch under dryland conditions.…”
Section: Crop Residue Cover and Canopy Shadingmentioning
confidence: 99%
“…Reducing input costs in soybean by using lower seeding rates, especially when transgenic cultivars are planted which include substantial technology fees, is a reasonable approach to soybean production. While research has demonstrated that higher plant populations and narrow rows suppress weeds more effectively than lower plant populations or production in wider row spacings [14][15][16][17], Norsworthy and Oliver [18] reported that applying a second application of glyphosate was more economical than increasing the seeding rate. Kratochvil et al [19] reported that a population 80% of a traditional seeding rate (345,000 plants ha −1 versus 432,500 seed ha −1 ) increased profit from $14 to $28 ha −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Embora seja consenso que a variabilidade na distribuição longitudinal de plantas na linha de semeadura do milho pode influenciar as competições intraespecíficas (Brachtvogel et al, 2012) e interespecíficas (Nice et al, 2001) pouco se tem estudado sobre os métodos de avaliar esta regularidade e os fatores que a influenciam.…”
Section: Introductionunclassified